A united front: Coach and teammate motivational climate and team cohesion among female adolescent athletes - Weiss, M. R.; Moehnke, H. J.; Kipp, L. E. (International Journal of Sports Science & Coaching, 2021)
Based on theory and research on athlete motivation and sport cohesion, this study examined the concurrent association of perceived coach and peer motivational climates with team cohesion among female adolescent athletes. Participants (N = 235) included 14- to 18-year-old competitive volleyball players who completed self-report measures of motivational climates and team cohesion in the latter part of the season. Canonical correlation analysis revealed that all coach and peer task-involving dimensions were positively related, and peer intra-team conflict (ego-involving dimension) was negatively related, to team cohesion. Task-involving dimensions of coach cooperative learning and peer effort and relatedness support contributed most strongly to the relationship as did task cohesion. Multiple regression analyses showed that elements of both coach and peer climates were related to task and social cohesion. Findings extend past research by simultaneously examining coaches and peers as social sources of team cohesion among female adolescent athletes. Specific strategies are offered for how coaches can enhance team cohesiveness by directly shaping a task-involving climate, minimizing an ego-involving climate, and fostering a teammate task-involving climate that promotes positive peer interactions and relationships.